New evidence of an Ediacaran age for the Bambui Group in southern Sao Francisco craton (eastern Brazil) from zircon U-Pb data and isotope chemostratigraphy - Paula-Santos, Gustavo Macedo; Babinski, Marly; Kuchenbecker, Matheus; Caetano-Filho, Sergio [UNESP]; Trindade, Ricardo Ivan; Pedrosa-Soares, Antonio Carlos (Elsevier B.V., 2015)
Extensive carbonate-siliciclastic successions of the Bambui Group, which overlie Neoproterozoic glaciogenic diamictites, cover most of the southern Sao Francisco craton (eastern Brazil). This group records sedimentation in a foreland setting related to the diachronic orogenic processes that formed the Brasilia and Aracuai marginal belts. The lowermost unit of the Bambui Group, the Sete Lagoas Formation, comprises two shallowing-upward sequences of carbonate rocks with subordinated pelitic intercalations, overlying the glaciogenic diamictites in the southern Sao Francisco Craton. This study combines isotope chemostratigraphy (C, O, Sr) and U-Pb dating of zircon detrital grains retrieved from marls of the Sete Lagoas Formation. The basal sequence comprises low organic matter limestones and dolostones with delta C-13 values around 0 parts per thousand, positioned above cap carbonates dated at around 740 Ma (Pb-Pb whole-rock isochron). The U-Pb ages obtained for this sequence show several age peaks between 1270-870 Ma and 625-550 Ma. The upper sequence includes dark limestones with delta C-13 values as high as +10 parts per thousand, best preserved Sr-87/Sr-88 ratios of around 0.7075 and U-Pb ages ranging from 625 Ma to 550 Ma. Our geochronological data suggest that the Aracuai orogen is the main source of sediment for the Sete Lagoas Formation, and the youngest zircon population sets the maximum depositional age for its upper part at around 557 Ma. This suggests that the studied section of the Sete Lagoas Formation is not related to either the Sturtian or the Marinoan glacial events. Also, the Sr-87/Sr-86 ratios obtained from Sete Lagoas carbonates contrast with Sr evolution curves available in the literature, especially with those for the Ediacaran-Cambrian limit, when ratios higher than 0.7080 would be expected. The same discrepancy is reported for other Ediacaran carbonate successions, pointing to local disturbances in Sr composition of marine basins rather than global processes. Interbasinal correlations and blind dating based on isotope chemostratigraphy should proceed carefully, especially for Ediacaran marine deposits located on the inner parts of large palaeocontinental regions, such as those found in western Gondwana. (C) 2014 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Bambui Group; Sao Francisco craton; U-Pb dating; Sr isotopes